ANALISIS PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - Jonnadi, Arius; Amar, Syamsul; Aimon, Hasdi (Jurnal Kajian Ekonomi, 2012)
ABSTRACT Economic growth and poverty is an important indicator to see the success of a country's development. This study aims to determine and analyze the two-way influence   between   economic   growth   and   poverty   in   Indonesia:   (1)   The   effect   of unemployment,        poverty,   investments      and   economic     growth.     (2)  The   effect   of investment,     life  expectancy,     literacy,   and   length   of  education,     and   economic growth   on   poverty.This   study   uses   panel   data   or   pooled   time-series   crossection using time series data from the years 2005-2009, and the crossection is that there are 33 provinces in   Indonesia. The method used is descriptive and econometric analysis     using   a   model    of   simultaneous      equations     (simultaneous      equations models)   with   two-stage   least   squares   method   (Two-Stage   Least   Square   2SLS) using Indirect Least Square (ILS). The   results   showed   that   there   is   a   two-way   interplay   between   economic growth and poverty. Significant effect on economic growth in poverty reduction, especially   in   rural   areas    there   are   many   pockets    of  poverty.   the   opposite   of poverty is also a significant effect on economic growth. Through improved access to capital, quality of education (literacy and increased length of education) and health (increased life   expectancy) of the poor can increase their productivity in the attempt during the period 2000-2009. The unemployment rate, and significant investment      on   economic     growth.     Furthermore,      investments     in   domestic    and foreign investments,  life expectancy, literacy and school longer a significant effect on the number of poor. Based     on  these   findings    the  policy   the  government      should    do   is  spur economic   growth   through   the   expansion   of   investment   especially   in   agriculture (agribusiness      and    agro-industries)     in  rural    areas   where     many    poor    people depend.   Recommended   to   the   government   in   order   to   spur   economic   growth   in urban areas in order to prioritize employment in which informal sector in general the   poor   do   business.    Whereas     in  rural   areas   run  projects    that  are   capital - intensive    investment     to  open    up   employment      opportunities,     especially    in  the agricultural sector. Furthermore, it also advised the government both at central and   regional   levels   through   the   state   budget   and   regional   budgets   in   order   to further enhance the percentage of budget allocation on health and education to improve   the   quality   of   human   resources   of   Indonesia's   population.   In   order   to improve      the   quality   of   human     resources     in   Indonesia     suggested     that   the government should also  continue to run the program compulsory 9 (nine) years, and scholarships for children from poor families to achieve to improve the quality of their children. Keyword: Economic growth, poverty, unemployment, and investments